Purchasing Luxury Goods: consumer behaviour of international students in the UK - Srichan, Srichan (2007)
This study attempts to investigate young consumer behaviour towards purchasing luxury brand products in three countries including the United Kingdom,Thailand and China. It describes the results from a survey of 144 students at various Universities in the UK. Snowball sampling method was applied to distribute online questionnaire. In this study, the statistical data analyses in a form of SPSS with the help of Microsoft Excel were conducted by applying a method of inferential statistics T-test and F-test. The combinations of qualitative and quantitative were used to aid the explanation of the results. This work mainly focuses on culture, motivation, status and material consumption, generation Y and gender. It indicates that there has been a change in culture suggesting that Eastern consumers purchasing preferences appears to imitate Western style behaviour. In terms of purchasing luxury brand items, UK and Thai consumers seems to have the same motivational factors whereas Chinese respondents show a different perspective. Status and materialistic consumption have been identified to show respondents behaviour and the purpose to why they purchase luxurious products in which UK and Thai respondents do not purchase products to show status or for possessive reasons; however, some Chinese respondents have shown some relation. The focus on generation Y has been applied to this study to show that teens have the same purchasing preferences and that products can be standardized worldwide. Additionally, there seems to be no relation towards gender and consumers behaviour towards purchasing luxury brand products.